Formulation and Development of Famotidine Solid Dispersion Tablets for their Solubility Enhancement - Rajendra, Shirsath Nitin; Vaibhavkumar, Jagtap; Kamalgiri, Goswami Ajaygiri (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Famotidine is BCS class II drug having a low aqueous solubility and low oral bioavailability. It needs to develop into its novel form for solubility and dissolution rate enhancement. Materials and Methods: The aim of the current work was to formulate famotidine (FAM)-poloxamer 188 solid dispersions (SDs) by kneading method for solubility enhancement. The problems of low solubility were eliminated by preparing the SDs using the poloxamer 188 as hydrophilic carrier. Results and Conclusion: The prepared tablets of SDs were characterized by employing solubility, FTIR, disintegration test, friability, wetting time and in-vitro drug release. The optimum values of solubility and in-vitro drug release of prepared novel formulation were maximum than conventional dosage form. The famotidine (FAM)-poloxamer 188 solid dispersions were successfully prepared and seem to be promising for enhanced dissolution rate (solubility) and oral bioavailability.
Keywords: Solid dispersions (SDs); Kneading method; Famotidine; Solubility; Dissolution; rate; Bioavailability